The letters [videorecording (DVD)] - Riead, William; Stevenson, Juliet; Hauer, Rutger, 1944-2019-; Sydow, Max von, 1929-2020- (Twentieth Century Fox Home Entertainment, 2016)
Based on the true story of Mother Teresa, the film explores the life's work of the Nobel Peace Prize recipient and one of the greatest humanitarians of all time. Her selfless devotion to helping the poor changed hearts, transformed lives and inspired millions throughout the world. Told through a series of personal letters written to her longtime friend and spiritual advisor.